Influence of Maternal Preeclampsia on Neurodevelopmental Outcomes of Preterm Infants - Halil Degirmencioglu; Birgul Say; Zeynep Ustunyurt; Serife Suna Oguz (Medical Network, 2018)
Objective: The aim of this study was to determine the neurodevelopmental outcome of preterm infants born to mothers with preeclampsia and to compare them with preterm controls. Study design: This was a retrospective, observational study in a large, tertiary, neonatal intensive care unit. Neurodevelopmental evaluations using Bayley Scales of Infant Development II were performed in 226 two-year-old infants with birth weight ≤1500 g and gestational age ≤32 weeks who were born to mothers with preeclampsia and in 493 infants who were born after normotensive pregnancies, matched for gestational age and gender. Results: The mean gestational ages of the infants in the preeclampsia and control groups were 29.9±2.3 weeks and 28.7±4.1 weeks, respectively (p<0.001). A total of 372 infants with a mean age of 19.2±3.2 months were assessed for long-term outcome. The mean mental developmental index score was significantly higher, and the percentage of infants with cerebral palsy was significantly lower, in the preeclampsia group compared with the control group (p=0.03 and p=0.02, respectively). However, no overall significant differences in neurodevelopmental impairment rates were found between the two groups (p=0.08). Conclusion: Maternal preeclampsia seems to be a protector factor for the development of cerebral palsy in preterm infants.